Negative valence specific deficits in judgements of musical affective quality in alexithymia. Issue 3 (3rd April 2021) - Larwood, Joel L.; Vanman, Eric J.; Dingle, Genevieve A.
ABSTRACT: Alexithymia is characterised by a lack of words for emotional experiences and it has been implicated in deficits in emotion processing. Research in this area has typically focused on judgements of discrete emotions rather than of affect, which is a precursor to emotion construction. In the current study, higher alexithymia was predicted to be related to more neutral judgements of valence and arousal of music representing a range of emotions. Participants ( N  = 162) listened to ten 15-second musical pieces that represented five target emotions (happy, sad, tender, angry, and fearful) and rated the valence and arousal of each. Participants also listed emotion words they knew to be expressed in music. Analyses revealed that alexithymia was not related to the number of emotion words generated but was related to valence-specific affect judgements of music. Participants higher in alexithymia rated sad, angry, and fearful pieces as more neutral in valence and arousal. Alexithymia was not related to ratings of valence or arousal for happy and tender pieces. These findings suggest that perceptual deficits in alexithymia may be specific to negative emotions. Our results are consistent with the idea that alexithymia is related to the direction of attention away from negative stimuli.